Self-referential false associations: A self-enhanced constructive effect for verbal but not pictorial stimuli. Issue 9 (September 2021) - Wang, Jianqin; Otgaar, Henry; Howe, Mark L; Cheng, Sen
Memory is considered to be a flexible and reconstructive system. However, there is little experimental evidence demonstrating how associations are falsely constructed in memory, and even less is known about the role of the self in memory construction. We investigated whether false associations involving non-presented stimuli can be constructed in episodic memory and whether the self plays a role in such memory construction. In two experiments, we paired participants' own names (i.e., self-reference) or the name "Adele" (i.e., other-reference) with words and pictures from Deese/Roediger–McDermott (DRM) lists. We found that (1) participants not only falsely remembered the non-presented lure words and pictures as having been presented, but also misremembered that they were paired with their own name or "Adele, " depending on the referenced person of related DRM lists; and (2) there were more critical lure–self associations constructed in the self-reference condition than critical lure–other associations in the other-reference condition for word but not for picture stimuli. These results suggest a self-enhanced constructive effect that might be driven by both relational and item-specific processing. Our results support the spreading-activation account for constructive episodic memory.